Nickel catalyst with outstanding activity in the DRM reaction prepared by high temperature calcination treatment. (1st June 2016) - Smoláková, Lucie; Kout, Martin; Čapek, Libor; Rodriguez-Gomez, Alberto; Gonzalez-Delacruz, Víctor M.; Hromádko, Luděk; Caballero, Alfonso
Abstract: The catalytic performance of some NiCe/Al2 O3 catalytic systems (11 wt.% Ni and 3 wt.% Ce) were checked after being submitted to different calcination and reduction treatments. It was found that, the reduced NiCe/Al2 O3 catalysts were more active and stable in the dry reforming reaction of methane than the corresponding not-reduced catalysts. This high activity was initially connected with the smaller size of pre-reduced Ni species, which at the same time leads on to the formation of filamentous carbon. The best overall performance was obtained for the reduced catalyst after being calcined at 1000 °C. This catalyst presents a very high stability, a low level of carbon formation, maintaining the nickel particle size constant during reaction. Surprisingly, although its reduction degree is only 12% at 750 °C, its catalytic activity is similar to the full reduced catalysts. So, the small number of reduced metallic particles of this catalyst shows a very high activity, much higher than the other catalysts. Highlights: The effect of calcination on nickel supported catalysts has been established. A subsurface Ni aluminate phase has been formed by calcination. Reduction improves the catalytic performances in the DRM reaction. Metal support interaction assures the stability of metallic particles. An outstanding specific activity has been observed for the higher calcination temperature.